Depositing Molecular Graphene Nanoribbons on Ag(111) by Electrospray Controlled Ion Beam Deposition: Self‐Assembly and On‐Surface Transformations. (16th February 2022) - Ran, Wei; Walz, Andreas; Stoiber, Karolina; Knecht, Peter; Xu, Hongxiang; Papageorgiou, Anthoula C.; Huettig, Annette; Cortizo‐Lacalle, Diego; Mora‐Fuentes, Juan P.; Mateo‐Alonso, Aurelio; Schlichting, Hartmut; Reichert, Joachim; et al.
Abstract: The chemical processing of low‐dimensional carbon nanostructures is crucial for their integration in future devices. Here we apply a new methodology in atomically precise engineering by combining multistep solution synthesis of N‐doped molecular graphene nanoribbons (GNRs) with mass‐selected ultra‐high vacuum electrospray controlled ion beam deposition on surfaces and real‐space visualisation by scanning tunnelling microscopy. We demonstrate how this method yields solely a controllable amount of single, otherwise unsublimable, GNRs of 2.9 nm length on a planar Ag(111) surface. This methodology allows for further processing by employing on‐surface synthesis protocols and exploiting the reactivity of the substrate. Following multiple chemical transformations, the GNRs provide reactive building blocks to form extended, metal–organic coordination polymers. Abstract : N‐doped molecular graphene nanoribbons, deposited by electrospray controlled ion beam deposition, form extended, metal–organic coordination polymers after multiple chemical transformations employing on‐surface synthesis protocols. These transformations and the nature of the metal–organic coordination motifs are investigated by high‐resolution scanning tunnelling microscopy.